Perkembangan Permukiman di Kecamatan Amurang Timur - Marbun, Mei Randa Ronatio; Lobja, Xaverius Erick; Kumaat, Joyce Christian; Rewah, Fonny (Fakultas Ilmu Sosial dan Hukum, 2024)
This study aims to identify the development of settlements in the Amurang Timur District. The method used is quantitative researchÃ¢â‚¬â€data collection techniques in the form of observation, documentation, and remote sensing. Researchers use GIS analysis techniques on Landsat 7 and Landsat 8 images. The results of the study show that the development of settlements in Amurang Timur District is influenced by population growth from 2015-2022, there was an increase in settlements of 92.49 hectares. The exponential population growth rate in 2015-2022 was 1.55%.